Evaluating the impact of water protection policy on urban growth: A case study of Jiaxing. (May 2023) - Guan, ChengHe; Gómez, Jairo A; Tripathy, Pratyush; Duque, Juan C; Passos, Santiago; Cheng, Tong; Li, Ying; Keith, Michael
Source water protection can be a greater challenge in cities where the hydric resource is deeply embedded within a rapidly growing urban area. In these types of cities, the delimitation of protection areas along water resources, as one of the main mechanisms for water resource protection, has a direct impact on the way the urban form evolves. On the one hand, narrow protection areas may not be enough to guarantee that the built city does not affect water levels and quality. On the other hand, wide protection areas can result in a fragmented city, with low levels of accessibility and tendencies towards dispersed and disorderly growth. In this article we use the city of Jiaxing, China, as a case study to determine what the optimal size of water protection areas might be. For this, we use two urban growth models and simulate various urban growth scenarios between 2020 and 2040. The results indicate that a protection area of 400 m guarantees a good level of protection of the water resource and a sufficient availability of land that allows an efficient urban growth.